Pengaruh Penggunaan Media Audiovisual Terhadap Hasil Belajar Tari Siswa Di SMA Negeri 1 Tanjung Mutiara - Putri Pernanda; Fuji Astuti (SENDRATASIK UNP, 2021)
This study aims to determine whether audio-visual media affects the dance learning outcomes of students in class X MIPA 2 at SMA Negeri 1 Tanjung Mutiara. This research is an experimental study whose population was the students at SMA Negeri 1 Tanjung Mutiara. The variables in this study were the independent and dependent variables. The research instrument used objective questions. The data were analyzed by using normality test and hypothesis test. The results showed that there are differences in students’ dance learning outcomes between the use of Audio Visual media and poster media in the even semester learning at SMAN 1 Tanjung Mutiara. This can be seen from the average value of the experimental class learning outcomes. The score got is 70.19. Meanwhile, the average value of learning outcomes in the control class is 60.19. It is also proved by the result of hypothesis testing where the Sig. (2-tailed) is 0.000 <from 0.05. These mean that H1 is accepted and H0 is rejected. Thus, there is a significant influence on the use of audiovisual media on student dance learning outcomes at SMA Negeri 1 Tanjung Mutiara.